Improving The Welfare of Street Children with The Concept of Social Entrepreneurship in Majalaya District - Lestari, Mia; Rachmani, Nizza Nadya; Koeswandi, Tika Annisa Lestari (Universitas Pendidikan Indonesia, 2021)
This article discusses solutions to social problems in Majalaya District, namely street children. Street children should be protected and their rights guaranteed as children in general, in order to become useful human beings and have a bright future. Currently, the handling of street children has begun to be activated properly. It can be seen from the number of shelter houses, orphanages, and studios that facilitate street children in developing themselves with education and soft skills. By being oriented to a social mission, or in this case to help provide the welfare of street children, the concept of social entrepreneurship can be used. Through the use of the embedded social enterprise model and the franchise model, where social enterprises are designed to achieve the goal of creating social and economic value, it will be suitable to be applied in a container to accommodate street children.